Comparative evaluation of novel tooth brushing with reminder therapy with conventional brushing techniques in children - S., Shilpa; Setty, Jyothsna V.; V., Srikanth K.; Srinivasan, Smrithi; Haridasan, Ajith Kumar; Srinivasan, Ila (International Journal of Contemporary Pediatrics, 2024)
Background: Dental caries and periodontal diseases are the most prevalent oral diseases in the children. Dental plaque is the main contributing agent for these oral diseases. Tooth brushing is considered to be one of the most efficient ways of maintaining the oral hygiene. Often, it is noted that certain areas of oral cavity and surfaces of the teeth are brushed more, while the other areas are neglected. With this background, we have designed a novel technique of tooth brushing with reminder therapy. Methods: Oral examination of 180 children aged between 6-12 years was done and Oral Hygiene Index Simplified, Turesky-Gilmore-Glickman modification of Quigley-Hein Plaque Index, Modified Gingival Index were recorded. The children were randomly divided into three groups; Control group; Tooth brushing using Fones technique; Tooth brushing along with a reminder therapy (dantharaag: the tooth tune). Each group was taught their respective techniques and follow up was done at 15 and 45 days interval and all the indices were recorded. The data, thus collected was tabulated and subjected to analysis. Results: The results showed a reduction in the scores of OHI-S, TMQH and MGI in all the three groups during follow up visits. However, this difference was statistically significantly between the groups where, Group 2 was better than Group 1 and Group 3 was better than Group 1 and 2 by 45 days. Conclusions: In conclusion, Dantharaag: the tooth tune was readily accepted by children and showed better results in plaque reduction and oral hygiene improvement.